1984
DOI: 10.1093/clinchem/30.6.906
|View full text |Cite
|
Sign up to set email alerts
|

Influences of specimen processing and storage conditions on results for plasma ammonia.

Abstract: Ammonia concentrations in plasma may increase because of contamination and deterioration of blood components during specimen handling and storage. Using replicate specimens from healthy volunteers, we studied influences of specimen processing and storage procedures on ammonia measurements made with a self-contained reagent system. Under some conditions, ammonia concentrations more than doubled. The use of nonhemolyzed plasma specimens and prompt centrifugation, separation of plasma, and ammonia determination a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 0 publications
0
40
1
Order By: Relevance
“…The rates of increase estimated in these studies ranged from only 2-4 µmol/L per hour at 0-4 o C, and 5-6 µmol/L per hour at 20-22 o C, although confidence limits on these rates of increase were not given. 4,6 In our study, we observed no statistically significant difference in plasma ammonia concentrations after heparinized whole blood was held for 5, 15, or 30 minutes either "on ice" or at room temperature. These findings were not unexpected, after extrapolating the published hourly rates of increase in ammonia concentration back to the time points that we examined, and given the published analytical standard deviations for current methods for measuring ammonia.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…The rates of increase estimated in these studies ranged from only 2-4 µmol/L per hour at 0-4 o C, and 5-6 µmol/L per hour at 20-22 o C, although confidence limits on these rates of increase were not given. 4,6 In our study, we observed no statistically significant difference in plasma ammonia concentrations after heparinized whole blood was held for 5, 15, or 30 minutes either "on ice" or at room temperature. These findings were not unexpected, after extrapolating the published hourly rates of increase in ammonia concentration back to the time points that we examined, and given the published analytical standard deviations for current methods for measuring ammonia.…”
Section: Discussioncontrasting
confidence: 43%
“…These findings were not unexpected, after extrapolating the published hourly rates of increase in ammonia concentration back to the time points that we examined, and given the published analytical standard deviations for current methods for measuring ammonia. 4,6,11 In a recent retrospective study, Hashim and Cuthbert examined the plasma ammonia results for over 1,800 patients, where samples were collected in EDTA and transported on ice. They found no significant relationship between ammonia levels and pre-analytical time up to 30 minutes, and concluded that ammonia results are reliable if the total time that elapses from collection to result is <120 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is thus impossible to send samples to a specialized laboratory by mail. [42][43][44][45][46] Although several authors mention this problem as the main reason for avoiding the use of AMM tests, this disadvantage has been largely resolved by the introduction of the Blood Ammonia Checker II. e This analyzer proved to be a simple, reliable, and relatively inexpensive alternative to the standard automated enzymatic assay.…”
Section: Discussionmentioning
confidence: 99%